Rituximab in pemphigus and pemphigoid patients: Treatment outcomes and safety profile - A 6-year tertiary center study - Sivakanth Gopakumar; Nima Teresa Andrew; Maria Jose; Sanitha Kuriachan; Jumi Jacob (Asian Journal of Medical Sciences, 2025)
Background: Pemphigus and pemphigoid are autoimmune blistering disorders characterized by autoantibodies attacking skin and mucous membranes. Rituximab, targeting CD20-positive B cells, has emerged as a treatment option for resistant cases. Aims and Objectives: To evaluate the treatment outcomes and safety profile of rituximab in patients with pemphigus and pemphigoid diseases treated at a tertiary care center over 6 years. Materials and Methods: This retrospective study analyzed the outcomes of 23 patients treated with rituximab for pemphigus and pemphigoid diseases at a tertiary care hospital between February 2017 and February 2023. Data included demographics, disease characteristics, treatment specifics, and adverse reactions. Treatment response was evaluated using the Nikolsky sign, and the World Health Organization causality assessment scale classified adverse events. Statistical analysis was conducted with SPSS version 25.0. Results: The study included 23 patients (52.2% male), with a mean age of 50.48 years. Majority of the patients were diagnosed with pemphigus vulgaris (60.9%). Of the 23 patients, 17 (73.9%) achieved complete remission, while 6 (26.1%) attained partial remission. Most patients (43.5%) required two cycles of rituximab, with complete remission achieved after two cycles in 52.9% of those in remission. Patients with partial remission required more infusions, with 33.3% receiving three or more cycles. Adverse drug reactions (ADRs) were observed in 5 patients (21.7%), all of whom experienced mild, infusion-related symptoms, such as pruritus (8.7%) and dyspnea (4.3%). A significant association between gender and ADRs was found, with females more prone to ADRs (P=0.008). No severe reactions were reported, and all ADRs were resolved. Conclusion: Rituximab shows high efficacy in inducing remission in pemphigus and pemphigoid patients, with a manageable safety profile. Individualized treatment regimens, including the number of cycles, may optimize outcomes.